Nano‐ and Micro‐Structures Formed during Laser Processing of Selenium Doped Bismuth Telluride. Issue 15 (2nd July 2021) - Welch, Ryan; Hobbis, Dean; Birnbaum, Andrew J.; Nolas, George; LeBlanc, Saniya
Abstract: Laser processing of thermoelectric materials provides an avenue to influence the nano‐ and micro‐structure of the material and enable additive manufacturing processes that facilitate freeform device shapes, a capability that is lacking in thermoelectric materials processing. This paper describes the multiscale structures formed in selenium‐doped bismuth telluride, an n‐type thermoelectric material, from laser‐induced rapid melting and solidification. Macroscale samples are fabricated in a layer‐by‐layer technique using laser powder bed fusion (also known as selective laser melting). Laser processing results in highly textured columnar grains oriented in the build direction, nanoscale inclusions, and a shift in the primary charge carriers. Sparse oxide inclusions and tellurium segregation shift the material to p‐type behavior with a Seebeck coefficient that peaks at 143 µV K –1 at 95 °C. With an average relative density of 74%, fabricated parts have multiscale porosity and microscale cracking that likely resulted from low powder layer packing density and processing parameters near the transition threshold between conduction and keyhole mode processing. These results provide insights regarding the pathways for influencing carrier transport in thermoelectric materials via laser melting‐induced nanoscale structuring and the laser processing parameters required to achieve effective powder consolidation and hierarchical structuring in thermoelectric parts. Abstract : The transport properties, multiscale features, and thermoelectric properties of laser processed n‐type bismuth telluride are reported. Laser processing causes a highly textured grain structure, nanoscale inclusions, tellurium segregation, and a change in primary charge carriers. Sparse oxide inclusions and tellurium segregation influence a Seebeck coefficient shift, suggesting the material becomes p‐type after laser processing.